(untitled) (Acta Medica Academica, 2013)
The aim of this review is to give an overview of 55 years experience of milk fluoridation and draw conclusions about the applicability of the method. Fluoridated milk was first investigated in the early 1950s, almost simultaneously in Switzerland, the USA and Japan. Stimulated by the favourable results obtained from these early studies, the establishment of The Borrow Dental Milk Foundation (subsequently The Borrow Foundation) in England gave an excellent opportunity for further research, both clinical and non-clinical, and a productive collaboration with the World Health Organization which began in the early 1980s. Numerous peer-reviewed publications in international journals showed clearly the bioavailability of fluoride in various types of milk. Clinical trials were initiated in the 1980s – some of these can be classed as randomised controlled trials, while most of the clinical studies were community preventive programmes. Conclusion. These evaluations showed clearly that the optimal daily intake of fluoride in milk is effective in preventing dental caries. The amount of fluoride added to milk depends on background fluoride exposure and age of the children: commonly in the range 0.5 to 1.0 mg per day. An advantage of the method is that a precise amount of fluoride can be delivered under controlled conditions. The cost of milk fluoridation programmes is low, about € 2 to 3 per child per year. Fluoridation of milk can be recommended as a caries preventive measure where the fluoride concentration in drinking water is suboptimal, caries experience in children is significant, and there is an existing school milk programme.